WEBSITE MAKING ONLINE KOI FISH SHOP - Devi Indriani; Muhammad Muflih Naufal (Asosiasi Dosen Muda Indonesia, 2022)
During the COVID-19 pandemic, this triggers the use of technology that is carried out online. Currently, the Koi fish shop is still using the conventional sales system, where customers come directly to the shop so that they can be served as well as the buying and selling process, where buyers come directly to see the fish they want to buy or their accessories. Customers who are interested in the accessories and fish offered at the Koi Shop, the transaction process directly occurs at the store. Based on these needs, a koi fish online shop website was created. The koi fish shop website uses the PHP programming language and MySQL as the database. Making this web refers to the SDLC (System Development Life Cycle) stage, including the planning, analysis, design, implementation and testing phases. Customers can register an account in advance to be able to place orders and make payments. Product orders can be accessed on various platforms, namely computers and smartphones. With the existence of this website, it is hoped that the koi fish shop can grow more in terms of sales and attract customers. Sourced from the browser and device test table, the application runs well and the display corresponds to the original on the Google Chrome and Mozilla Firefox browsers, while Microsoft Edge takes time to display properly and the application runs well, neatly and in accordance with the original on the smartphone device installed on the device test.